(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: To find the association between neck pain & disability with hand grip strength among dentists of Rawalpindi and Islamabad. Materials and Methods: This descriptive observational study was conducted after the approval from the ethical review committee of University of Lahore Islamabad Campus. A 379 sample size was calculated by using open Epi-tool calculator and sample was raised through non-probability convenient sampling technique. Data collection tools included semi-structured questionnaire and Urdu version of Neck Bournemouth Questionnaire to assess neck pain and Camry Electronic Dynamometer to measure grip strength of right and left hand. Data was analyzed by SPSS version 27. Subjects who satisfied the inclusion criteria volunteered to participate in the study. Results: The Pearson’s correlation coefficient was used. The results of this study shows that there was weak negative correlation between the hand grip strength of left hand (r= -0.17) and right hand (r= -0.12) with neck pain and a significant value of <0.01. Conclusion: This study shows weak negative correlation between the neck pain and hand grip strength. So increase in neck pain leads to decrease in hand grip strength.